Outcomes of Outpatient Parenteral Antimicrobial Therapy With Ceftriaxone for Methicillin-Susceptible Staphylococcus aureus Bloodstream Infections—A Single-Center Observational Study. (13th August 2020) - Hamad, Yasir; Connor, Lee; Bailey, Thomas C; George, Ige A
Abstract: Background: Staphylococcus aureus bloodstream infections (BSIs) are associated with significant morbidity and mortality. Ceftriaxone is convenient for outpatient parenteral antimicrobial therapy (OPAT), but data for this indication are limited. Methods: Adult patients with methicillin-susceptible Staphylococcus aureus (MSSA) BSI discharged on OPAT with cefazolin, oxacillin, or ceftriaxone for at least 7 days were included. We compared outcomes of ceftriaxone vs either oxacillin or cefazolin. Ninety-day all-cause mortality, readmission due to MSSA infection, and microbiological failure were examined as a composite outcome and compared among groups. Rates of antibiotic switches due to intolerance were assessed. Results: Of 243 patients included, 148 (61%) were discharged on ceftriaxone and 95 (39%) were discharged on either oxacillin or cefazolin. The ceftriaxone group had lower rates of intensive care unit care, endocarditis, and shorter duration of bacteremia, but higher rates of cancer diagnoses. There was no significant difference in the composite adverse outcome in the oxacillin or cefazolin group vs the ceftriaxone group (18 [19%] vs 31 [21%]; P = .70), comprising microbiological failure (6 [6.3%] vs 9 [6.1%]; P = .94), 90-day all-cause mortality (7 [7.4%] vs 15 [10.1%]; P = .46), and readmission due to MSSA infection (10 [10.5%] vs 13 [8.8%]; P = .65). Antibiotic intolerance necessitating a change was similar between the 2 groups (4 [4.2%] vs 6 [4.1%]; P = .95). Conclusions: For patients with MSSA BSI discharged on OPAT, within the limitations of the small numbers and retrospective design we did not find a significant difference in outcomes for ceftriaxone therapy when compared with oxacillin or cefazolin therapy.